Do antenatal corticosteroids given prior to elective caesarean section in twin pregnancies at >37 weeks gestation improve neonatal outcome?. (7th June 2011) - Simcox, L; Neilson, J; Bricker, L
Abstract : Evidence from the ASTECS trial in 2005 has shown that antenatal corticosteroids reduce admissions to the neonatal unit with respiratory distress after elective caesarean section at term in singletons. Delivery at 37–38 weeks for twin pregnancies is common practice in the UK, and in 2009, we introduced a single course of antenatal corticosteroids for these women having an elective caesarean section. We performed a retrospective analysis of all twins delivered by elective caesarean section at ≥37 weeks between 2005 and 2010. We looked at 114 twin deliveries (228 babies) during this time period. One baby with a congenital abnormality was excluded. In total 76% (173) twins were not given steroids and 24% (54) twins were. In both groups, admission to the neonatal unit was 20%. Median duration of stay in days was 3 in the steroid group with a range of 0–13, compared to a median of 2 in the other group with a range of 0–7. One baby not given steroids was admitted because of respiratory distress syndrome and there were no cases of intraventricular haemorrahage, apgar <7 at 5 min, need for surfactant or necrotising enterocolitis. Delivery at ≥37 weeks for twins by elective caesarean section is associated with low morbidity overall. Corticosteroids prior to caesarean section do not appear to confer benefit but this would need to be evaluated in an adequately powered randomised controlled trial.